Green Human Resources Management in Supporting Environmental Performance at Six Senses Uluwatu, Bali - Yadnya, Putu Ayu Indira; Triyuni, Ni Nyoman; Sari, I Gusti Agung Mas Krisna Komala; Sadguna, I Gde Agus Jaya (Journal of Business on Hospitality and Tourism, 2023)
As a hotel that carries the concept of sustainability, it is very important to Six Senses Uluwatu, Bali to understand how green human resources management affects employees' environmentally friendly behavior, which in turn affects the company's environmental performance. Until now, the implementation of green human resources management has not been fully implemented at Six Senses Uluwatu, Bali, because there are still several things that hinder it. This research aims to analyze the implementation of green human resources management and to find out how green human resources management can support the environmental performance at Six Senses Uluwatu, Bali. This research uses a qualitative approach with data analysis techniques Miles and Huberman model, which consists of data reduction, data display, and conclusion drawing/verification. The implementation of Green Human Resources Management at Six Senses Uluwatu, Bali has been running at 75% so far. In addition, practices that have not been implemented are currently in the planning stage to be implemented in the future. Although it is not perfect, there is already a process in implementing green human resources management which is always reviewed and improved.